Child prosociality within HIV-affected contexts: the impact of carer ill-health and orphan status - Tucker, L; Govender, K; Kuo, C; Casale, M; Cluver, L (Taylor and Francis, 2016)
Considerable attention has been provided to the potential adverse outcomes for youth in the context of HIV and AIDS. Using data from a large community-based study on the psychosocial well-being of youth affected by HIV and AIDS, this paper advances a strength-based, resiliency perspective that is centred on the construct of prosociality. Data was derived from the Young Carers South Africa Project, where a cross-sectional household survey was conducted with 2,477 child-carer pairs in an HIV endemic community in the province of KwaZulu-Natal, South Africa. Analysis in this paper focuses on a subset of 2,136 child-carer pairs. Perceptions of child prosociality were assessed using the Prosocial Scale of the Strengths and Difficulties Questionnaire (SDQ). Both child and carer responses were obtained to provide insight into the functioning of carer-child dyads. Descriptive and inferential analysis was conducted to explore ratings of child prosociality across different relational contexts affected by HIV and involving care for orphaned youths. Dual-affected households, where carers are ill with opportunistic infections and youth are orphaned due to AIDS, yielded the highest discrepancies with carers reporting low child prosociality and children self-reporting high prosociality. Carer ill health appears to play a role in differentiating child prosociality across relational contexts. Further research is needed to explore child prosociality as a protective mechanism in high HIV-endemic communities.